Funding Research in Emergency Department Shared Decision Making: A Summary of the 2016 Academic Emergency Medicine Consensus Conference Panel Discussion. (27th November 2016) - Dodd, Kenneth W.; Berman, Amy; Brown, Jeremy; Carr, Brendan G.; Dunn, Patrick; Escobedo, Marcus; Gayer, Christopher; Grieser, Mira; Carpenter, Christopher R.; Hess, Erik P.; Grudzen, Corita R.
Abstract: As part of the 2016 Academic Emergency Medicine Consensus Conference, "Shared Decision Making in the Emergency Department: Development of a Policy‐relevant Patient‐centered Research Agenda, " a panel of representatives from the Office of Emergency Care Research, the Patient‐Centered Outcomes Research Institute, the American Heart Association, the John A. Hartford Foundation, and the Emergency Care Coordination Center were assembled to discuss funding opportunities for future research in this field. This article summarizes their discussion of funding priorities and examples of successfully funded projects related to shared decision making in emergency medicine.